In Silico Study to Assess Antibacterial Activity from Cladophora Sp. on Peptide Deformylase: Molecular Docking Approach - Yoni Rina Bintari; Rio Risandiansyah (Borneo Journal of Pharmacy, 2019)
Increasing antibiotic-resistant pathogenic bacteria is a severe problem in the world. Therefore, there is a need to identify new drugs from natural products and also new drug targets. Cladophora sp. is a marine organism which is known to have bioactive compounds and a potential antibacterial. On the other hand, Peptide Deformylase (PDf) may prove to be a novel drug target since it is crucial for native peptide functioning in most pathogenic bacteria. This study screens for PDf inhibition activity of compounds from Cladophora sp. using molecular docking approach and screening the binding affinity of bioactive compounds against the peptide receptor PDf using Pyrex Autodock Vina software. Docking results were stored and visualized using Biovia Discovery Studio and PyMOL ligand. Ligands were obtained from previous literature in PubChem, and receptor peptide PDf from pathogenic bacteria: Pseudomonas aeruginosa (PDB ID:1N5N), Escherichia coli (PDB ID:1BSK), Enterococcus faecium (PDB ID:3G6N) and Staphylococcus aureus (PDB ID:1LQW), was obtained from the peptide data bank. The results of this screening show with ligand the highest binding affinity against PDf of P. aeruginosa, E. coli, E. faecium, and S. aureus is stearic acid (-5.9 kcal/mol), eicosapentaenoic acid (-6.6 kcal/mol), stearic acid (-5.8 kcal/mol), and stearic acid (-6.2 kcal/mol) respectively. The binding of natural compounds from Cladophora sp. with PDf models may provide a new drug with a different drug target for antibacterial potential.